PENGARUH KOMBINASI MACAM ZPT DENGAN LAMA PERENDAMAN YANG BERBEDA TERHADAP KEBERHASILAN PEMBIBITAN SIRIH MERAH (Piper crocatum Ruiz & Pav) SECARA STEK - Eko Anang Budianto; Kaswan Badami; Ahmad Arsyadmunir (Universitas Trunojoyo Madura, 2013)
Medicinal plants is one of Indonesia's agricultural potential to be developed and one of the medicinal plants that have bright prospects for the development of red betel, because in addition to be consumed as a medicinal plant, also as an ornamental plant. Effect of combination treatment with a long range of ZPT different immersion able to stimulate root growth in cuttings of red betel. This study aims to determine the effect of PGR combination with a long range of different immersion to the successful breeding of red betel cuttings. The study was conducted at the experimental farm of Agricultural Faculty of the University Trunojoyo Madura, in January to April 2012. The research method used was Randomized Design Group (RAK) single factor with seven treatments and repeated four times. Range of ZPT is used there are two, namely IBA and NAA, while the use of immersion time is one hour, two hours and three hours. The results showed that the IBA with a three-hour long immersion gives a significant influence on the variable root length, root number and root dry weight, whereas NAA with the old one-hour immersion is a very real influence on the observations of variable length and dry weight of leaf buds.Keyword : red betel, ZPT, IBA, NAA